Overexpression of lamin B1 induces mitotic catastrophe in colon cancer LoVo cells and is associated with worse clinical outcomes - Izdebska, Magdalena (Int J Oncol, 2017)
Lamins are the major components of the nuclear lamina and play important roles in many cellular processes. The role of lamins in cancer development and progression is still unclear but it is known that reduced expression of lamin B1 has been observed in colon cancer. Thus, the aim of the present study was to elucidate the influence of LMNB1 upregulation on colon cancer cell line after treatment with 5-FU. The results indicate, that overexpression of LMNB1 induced dose-dependent cell death mainly by mitotic catastrophe pathway. Furthermore, after upregulation of this intermediate protein, lower expression of lamin A/C was observed. Moreover, we observed an increase in fluorescence intensity of nuclear β-catenin and decrease in cell-cell interaction area, that was connected with inhibition of colon cancer cells migration. We present the reorganization of actin filament and β-tubulin, because these cytoskeletal proteins are directly or indirectly linked with lamins, and analyzing publicly available mRNA data we show that patients with overexpression of LMNB1 are characterized by lower survival rates within the first 30 months from diagnosis. Summarizing our results, upregulation of LMNB1 induce mitotic catastrophe and only small percentage of apoptosis. Moreover, we showed inhibition of cell migration and promotion of cell-cell contact as a results of direct and indirect regulation of β-catenin, lamin A/C, actin and tubulin. However, it is possible that mitotic catastrophe cells in patients with colorectal cancer may be a reservoir of the cells responsible for faster disease progression, and further investigations are necessary to confirm this hypothesis.